PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATERI POKOK KINEMATIKA GERAK LURUS DI KELAS X SEMESTER I SMA NEGERI 1 SUNGGAL T.P. 2016/2017 - Jambak, Astri Vindi Denninta; Simatupang, Sehat (JURNAL IKATAN ALUMNI FISIKA, 2017)
Studies conducted to determine the effect of learning model Problem Based Learning on learning outcomes of students in the subject matter kinematics of rectilinear motion in the first semester of grade X SMAN 1 Sunggal T.P 2016/2017. This type of research is quasi-experimental. Sampling was done by cluster random sampling that class as an experimental class X3 and X4 class as a class contro. The instrument used is the achievement test and observation activities. The average value of pretest kleas 23.90 experiment and control class 21.33. The second data were normally distributed and homogeneous class. T test results obtained pretest thitung <ttable (1.48881 <1.997) H0 accepted means initial ability of students in the experimental class with students in the control class. Grades given experimental treatment with a learning model Problem Based Learning and classroom control with conventional learning models. Postes given on the second class with an average yield of 68.52 experimental class and control class 62.09. And the average value of the entire student activity during the learning with the learning model Problem Based Learning is 9.01 including a very active category. While the average value of the entire student activity during the learning with conventional learning model is 7.94 including the active category. Postes data processing results obtained t> t table (8.806> 1.668) Ha accepted which means no influence of the use of learning model Problem Based Learning in the subject matter kinematics of rectilinear motion in the first semester of grade X SMAN 1 Sunggal T.P 2016/2017.